2014
DOI: 10.1097/phh.0000000000000061
|View full text |Cite
|
Sign up to set email alerts
|

Moving From Policy to Implementation

Abstract: Supplemental Digital Content is Available in the Text.This article describes a process to implement an eligibility analysis for healthy food financing programs and shares lessons learned from administering the Pennsylvania, New York, and New Orleans healthy food financing programs over the course of the past 9 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…It also provides evidence to the scientific literature that suggests the issue of food deserts persists in the U.S. In recent years, researchers have started evaluating various impacts of the HFFI [ 43 , 44 , 45 , 46 , 47 ]; however, additional information is needed in the literature. Future findings from the IPRC-NOPREN project will describe the longitudinal changes to food availability, pricing, and marketing in the existing small food stores after the opening of new HFFI-supported chain supermarkets in Chicago and Rockford, IL, USA.…”
Section: Discussionmentioning
confidence: 96%
“…It also provides evidence to the scientific literature that suggests the issue of food deserts persists in the U.S. In recent years, researchers have started evaluating various impacts of the HFFI [ 43 , 44 , 45 , 46 , 47 ]; however, additional information is needed in the literature. Future findings from the IPRC-NOPREN project will describe the longitudinal changes to food availability, pricing, and marketing in the existing small food stores after the opening of new HFFI-supported chain supermarkets in Chicago and Rockford, IL, USA.…”
Section: Discussionmentioning
confidence: 96%
“…However, a recent evaluation of the Minneapolis Staple Food Ordinance found that corporate-owned stores made greater gains in complying with healthy stocking requirements compared to independently owned stores [ 52 ]. Therefore, such requirements should be coupled with financing initiatives [ 53 , 54 ] to help independently owned stores stock healthy foods (e.g., refrigerated storage) and community engagement to increase demand for healthy foods to support the commercial viability of such efforts [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the course of 5 years, $195 million supported more than 900 projects in multiple states across the country in order to create or renovate supermarkets and small stores in low-income urban and rural areas. One such project in Pennsylvania called the Fresh Food Financing Initiative showed success and influenced the creation of additional programs across the country [53].…”
Section: Improving Neighborhood Food Environmentsmentioning
confidence: 99%